AN EFFICIENT THREE COMPONENT ONE-POT SYNTHESIS OF -1,2,3,4-TETRAHYDRO-4-OXO- 6-(5-SUBSTITUTED 2-PHENYL-1H-INDOL-3-YL)-2-THIOXOPYRIMIDINE-5-CARBONITRILE AS ANTIMICROBIAL AND ANTITUBERCULAR AGENTS - WALMIK, PRABHAKER (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to synthesis of 1,2,3,4-tetrahydro-4-oxo-6-(5-substituted 2-phenyl-1H-indol-3-yl)-2-thioxopyrimidine-5- carbonitrile derivatives (4a-c). Methods: The structures of all these unknown compounds have been confirmed with the help of physical and spectral techniques such as IR, 1H, and 13C NMR and mass spectral data and these newly synthesized compounds were evaluated for in-vitro antimicrobial and antitubercular activities. Results: Screening studies have demonstrated that the newly synthesized compound 4a exhibited promising antimicrobial and antitubercular properties. Conclusion: The final results revealed that compound 4a exhibited promising antimicrobial and antitubercular properties when compared to the standard drugs.